Pathogenesis of coronavirus disease 2019-associated kidney injury. Issue 3 (May 2021) - Smith, Kelly D.; Akilesh, Shreeram
Abstract : Purpose of review: The current review summarizes the pathologic findings in kidneys from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-infected patients who have had autopsies or undergone biopsy, and the pathogenic mechanisms implicated in coronavirus disease 2019 (COVID-19)-associated kidney diseases. Recent findings: Direct infection of the kidney by SARS-CoV-2 is not common, and convincing morphologic evidence of substantive kidney infection by SARS-CoV-2 is lacking. Severe COVID-19-associated acute kidney injury is likely multifactorial and results from the physiologic disturbances and therapies used to treat this illness. COVID-19-associated collapsing glomerulopathy (COVAN) is seen almost exclusively in patients with apolipoprotein L1 high-risk genotypes with no evidence of direct infection of the kidney by SARS-CoV-2. Summary: The prevailing evidence does not support substantive or persistent infection of kidneys in COVID-19 and indirect means of tissue injury are favored, although a 'hit and run' model cannot be excluded. COVAN frequently occurs in patients with mild respiratory systems, suggesting that innate and adaptive immune responses to SARS-CoV-2 infection may provide the second hit needed for the development of collapsing glomerulopathy in susceptible individuals. Abstract : Supplemental Digital Content is available in the text